Insurance as Strategy for Flood Risk Management at Limpopo River Basin A decision making Process under Uncertainty - Mondlane, Avelino Isaias; Hansson, Karin; Popov, Oliver B. (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2013)
The Limpopo River Basin, one of the nine international rivers crossing Mozambique, historically has shown to be cyclically flooded, undermining the economic and social development of its four riparian countries. Local and external added efforts are always in place when floods occur. Nowadays there are recommended ex-ante instruments to prevent floods and one of the most applicable instruments worldwide is insurance. Most of the inhabitants, even governments, affected by Limpopo River Basin are poor, therefore our concern regards the viability to apply insurance as a strategy for flood risk management. Moreover our research investigates to what extent the application of insurance, within two identified communities as case study, might create an added value in the process of decision making on flood risk management for Limpopo River Basin.